Long-Term Behavioral Effects of Post-weaning Social Isolation in Males and Females - Walker, Deena M.; Cunningham, Ashley M.; Gregory, Jill K.; Nestler, Eric J. (Frontiers in Behavioral Neuroscience, 2019)
Adolescence is a developmental period associated with vast neural and behavioral changes which are accompanied by altered sensitivity to stimuli, both stressful and rewarding. Perturbations, especially stressful stimuli, during this period have been shown to alter behavior in adulthood. Social isolation rearing is one such perturbation. This review highlights the long-term behavioral consequences of adolescent social isolation rearing in rodents with a specific focus on anxiety- and addiction-related behaviors. Sex-specific effects are discussed where data are available. We then consider changes in monoaminergic neurotransmission as one possible mechanism for the behavioral effects described. This research on both normative and perturbed adolescent development is crucial to understanding and treating the increased vulnerability to psychiatric disorders seen in humans during this life stage.